A hyperbolic model of optimal cash balances. Issue 2 (22nd January 2019) - van der Burg, John; Song, Xiaojing; Tippett, Mark
ABSTRACT: We develop a hyperbolic cash management model based on the Pearson Type IV probability density which minimises extreme variations in firm cash balances. Since the moments for the Type IV probability density are in general undefined and maximum likelihood estimation is compromised by the non-algebraic nature of the Type IV normalising constant, parameter estimation is implemented using the minimum method. Empirical analysis shows that the Type IV density is highly compatible with the quarterly cash flow data of a randomly selected sample of 100 large U.S. corporations. In contrast, around 60% of the 100 corporations return Jarque–Bera test statistics which are incompatible with the Gaussian probability density.